The Inheritance System and Functional Changes of Niti Naik Mahligai Dance in Siulak Mukai Tengah, Kerinci Community Jambi Regency - Utari, I Dewa Ayu Sri; Abbas, Zaini Bin; Supenida, I Dewa Nyoman (Titian: Jurnal Ilmu Humaniora, 2025)
This study aims to explain the inheritance system and changes the function of dance Niti naik Mahligai community Siulak Middle Mukai Kerinci in Jambi. By using qualitative data, descriptive analytical method used is done with data collection techniques in which there are literature study, observation, interviews, and the data were analyzed. As to analyze the approach of science and art, as well as using multiple inheritance dance theory, change theory, and the theory of functions. The results of the study dance inheritance system Niti naik Mahligai a kinship system vertically as seen from the genetic mechanisms that they have a blood relationship. Besides, the system is legally customary inheritance is matrilineal system according to (maternal lineage). On the other hand changes the function of climbing Niti naik Mahligai dance influenced by modernization, technology, and is also influenced by internal and external factors. Abstrak Penelitian ini bertujuan untuk menjelaskan sistem pewarisan dan perubahan fungsi tari Niti Naik Mahligai pada Masyarakat Siulak Mukai Tengah Kabupaten Kerinci Jambi. Dengan menggunakan data kualitatif, Metode yang digunakan deskriptif analitis yang dilakukan dengan teknik pengumpulan data yang didalamnya terdapat studi pustaka, observasi, wawancara, kemudian data yang diperoleh dianalisis. Adapun untuk menganalisis menggunakan pendekatan ilmu budaya, serta menggunakan beberapa teori pewarisan tari, teori perubahan, dan teori fungsi. Hasil penelitian sistem pewarisan tari Niti Naik Mahligai merupakan sistem kekeluargaan secara vertikal yang dilihat dari mekanisme genetik yang masih mempunyai hubungan darah. Selain itu sistem pewarisan secara hukum adat adalah menurut sistem matrilineal (garis keturunan pihak ibu). Disisi lain Perubahan fungsi tari Niti Naik Mahligai dipengaruhi oleh modernisasi, teknologi, dan juga dipengaruhi faktor internal serta eksternal.